Adaptive identification of underwater glider using U-model for depth & pitch control under hydrodynamic disturbances - Abbasi, I. (Penerbit UTM Press, 2015)
This paper presents an adaptive identification method based on recently developed control oriented model called U-model for online identification of underwater glider. It is indicated from obtained results that the proposed technique can accurately and adaptively model nonlinearity and dynamics of underwater glider even in presence of hydrodynamic disturbances. Since the proposed identification U-model scheme is control oriented in nature, hence it can be further utilized to synthesize a simple law for depth and pitch control of glider. Â© 2015 Penerbit UTM Press. All rights reserved.